Analysis Of Factors Influencing Preparation For Hajj Departure In Kendal Regency In 2022/2023 - Fika Ni'matul Maula (International Journal of Economics Development Research (IJEDR), 2023)
Study This important done Because frequent pilgrimages done public in the process of implementation influenced by factors health, economy and social. Factor that will influence candidate pilgrims for Can leave. For That study This held on base A objective main that is For know factor what affects preparation pilgrimage departure in Kendal Regency in 2022/2023. Study This held with A method quantitative descriptive with base philosophy positivism with utilise method study regression. Research results show that in a manner simultaneous factor health 109,103, economic 76,405 and social influence 105,906 to preparation Hajj departure. The magnitude exerted influence independent variable on preparation pilgrimage departure by 52.7%. Whereas the remaining 47.3% were affected variables outside the research model like knowledge, psychology congregation, facilities service, activity physical, and travel